The Impact of Twitter Spaces in Speaking Skill for EFL Students - Sufidiana, Risda; Mustofa, Mutmainnah; Nashir, Abdun (STAI Miftahul Ula Nganjuk, 2023)
Developing online media for teaching is needed in order to engage a technology and a strategy in teaching. Twitter Spaces is a part of Twitter that the user could make a room and start discussion. Thus, this research conducted to see the impact of using this app in teaching speaking skill. This research used basic qualitative method. The participants are the first grade of Junior High School students. The result is there are obstacles in using Twitter Spaces as the media of learning English; the students never used this app before, Twitter Spaces limited the participants in the room, and a new link must be made when the host’s connection is unstable. The students felt comfortable using Twitter Spaces in speaking English because they don’t need to show their face. But there is no significant impact to them.